As políticas monetárias intervencionistas e o alcance do conceito “too big to fail” para além do sistema financeiro - Jorge, Plinio Augusto Lemos (2024)
This thesis, based on hypothetical-deductive methodology, with bibliographical research on doctrine, legislation, newsletters and news on the subject, aims to investigate the causes and consequences of the change in paradigms on the globally widespread policies of State intervention in the financial system that followed the subprime crisis in the United States, and whether the scope of actors included in the concept of “too big to fail” should include economic agents from other sectors of the economy. To this end, it debates the interventionist monetary policy formulated by Central Banks, mainly in the United States, Europe and Brazil, its relationship with the protection of financial institutions called too big to fail, and the change of a system, previously believing in the security of investments in public securities through banks, which are increasingly focused on investing in shares in the global capital market. To this end, it first discusses the concepts involving the definition of the financial market, and then addresses the lack of ballast in the global financial system and specifically the ballast in relation to the Brazilian currency (Real). Subsequently, it deals with the quantitative theory of money. Then, it looks at orthodox monetary policies. Afterwards, it deals with the so-called heterodox policies, with an incursion into the case of the Japanese crisis that began in the 1990s, specially in the too big to fail approach, and then on the historicity of the Western context of cultural and political-legal mutation in the financial and capital markets as presented in the thoughts of Howard Stanley Marks. Next, it discusses how such heterodox policies were adopted in the United States, the Euro Zone and Brazil, with emphasis in the too big to fail programs. In the following chapter, it addresses the use of financial bailouts in face of to big to fail companies, initially from financial institutions, in other market sectors, presenting investigations on the subject. Finally, it concludes that there is a need to carry out further studies on the implementation of “too big to fail” in sectors outside the financial market, in order to prevent a global crisis from happening again and in order to bring greater transparency to acts and practices. of large economic conglomerates in the most diverse economic environments.